Natural phenomena, natural disasters and votes : the case of La Niña in Colombia (2017)
"In 2010 and 2011 an event known as La Niña affected most of the Colombian municipalities. In literature, there are two measures that are usually used in order to account for wintry crises like this one: atypical rains and realized disasters. In the Colombian case, accounting for realized disasters and atypical rains do not produce the same results, and one channel through which this difference can be explained is Colombia humanitaria. Colombia Humanitaria was the governmcnt response to the wintry crisis in terms of disaster relief, but it responded only to the more visible aspect: realized disasters. While atypical rains have a negative effect On the share of votes incumbents, especially the president, receive, the effect of realized disasters seems to be positive. One possible explanation for this is that since Colombia Humanitaria is focused on realized disasters, municipalities with more disasters are more likely to receive attention and disaster relief". -- Tomado del resumen.